Influence of tillage and cropping sequence on the soil physical properties, water balance and water use efficiency of wheat (Triticum aestivum L.) and canola (Brassica napus) under rainfed-conditions in the Rȗens sub-region of the Western Cape - Vorster, Abraham Hercules (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.